Biogeochemical process in mangrove ecosystem - DEWI, APRILIA; DIANTI, -; KIRANA NURUL, ARIFIANI; AGUSTINA PUTRI, CAHYANINGSIH; LIA, KUSUMANINGRUM; SARNO, -; Khairul Adha, A. Rahim; AHMAD DWI, SETYAWAN (Society for Indonesian Biodiversity, 2020)
Aprilia DA, Dianti, Arifiani KN, Cahyaningsih AP, Kusumaningrum L, Sarno, Rahim KAA, Setyawan AD. 2020. Review: Biogeochemical process in mangrove ecosystem. Intl J Bonorowo Wetlands 10: 126-141. The mangrove ecosystem, one of the unique and distinctive aquatic ecosystems, is located in the tidal areas of the coast coastal areas in the tropics and subtropics. Mangrove ecosystems have many ecological, environmental, and social benefits. Mangrove forests have the potential to become a potential resource. This review aims to determine the process and function of the biogeochemical cycle in the mangrove ecosystem. The research method used in this research is descriptive qualitative research methods and tends to use inductive analysis. The biogeochemical cycle acts as a cycle that cannot be separated from the mangrove ecosystem. Biogeochemistry is the process of circulating chemical elements or compounds that occur repeatedly and continuously. Biogeochemistry plays a role in maintaining environmental stability and maintaining life on earth. The biogeochemical cycle consists of energy flow and nutrient cycling. Energy flows consist of food chains and food webs. The nutrient cycles include water, carbon, nitrogen, phosphorus, and sulfur. Various chemical elements resulting from the cycle process are needed to survive living things in the mangrove ecosystem.